The Factors Influencing on Consumption of Palm Cooking Oil in Indonesia - Teti, Ermy; Hutabarat, Sakti; Nofionna, Asriati (Economic Journal of Emerging Markets, 2011)
Cooking oil is one of the most sensitive basic needs in Indonesia. The aims of the research are to analyze factors influencing consumption of cooking oil, the cooking oil price, and the Crude Palm Oil price in Indonesia. Using simultaneous equation model, the study show that palm cooking oil consumption is significantly affected by domestic palm cooking oil price and number of population. Whilst palm cooking oil price is significantly influenced by the cooking palm oil production and the domestic Crude Palm Oil price. Finally, the domestic Crude Palm Oil is significantly affected by international Crude Palm Oil price. Keywords: consumption, cooking oil price, crude palm oil price and cooking oil